2009
DOI: 10.1111/j.1601-5223.1979.tb01288.x
|View full text |Cite
|
Sign up to set email alerts
|

Genesis of the 14q+ marker in Burkitt's lymphoma

Abstract: By means of the “prosome” analysis technique, by which chromosomes are studied at early metaphase and even at prophase, an improved resolution of the G‐band pattern has been achieved. The 2 chromosome regions of especial significance in the (8; 14) translocation of Burkitt's lymphoma, 8q24 and 14q32, which in the Pans karyotype were represented as uniformly negative, in prosome analysis resolved into 5 and 6 subbands respectively. The (8; 14) translocation was shown to be reciprocal and the breaking points cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Actually the segments involved in structural rearrangements exhibit the appearance of an earlier stage of banding differentiation, while the banding pattern of the unaffected segments of the same chromosomes display the same more condensed appearance as the rest of the chromosomes of the cell. The detailed band pattern of the 2 markers, marX/11 and marlI/X, described above is another example of local prosomization, as reported by MANOLOVA et al (1979) and . A similar effect was recently reported by HECHT and KAISERMCCAW…”
Section: During Remission Before Relapsementioning
confidence: 55%
See 1 more Smart Citation
“…Actually the segments involved in structural rearrangements exhibit the appearance of an earlier stage of banding differentiation, while the banding pattern of the unaffected segments of the same chromosomes display the same more condensed appearance as the rest of the chromosomes of the cell. The detailed band pattern of the 2 markers, marX/11 and marlI/X, described above is another example of local prosomization, as reported by MANOLOVA et al (1979) and . A similar effect was recently reported by HECHT and KAISERMCCAW…”
Section: During Remission Before Relapsementioning
confidence: 55%
“…The fact that so many primary chromosome changes in cancer are expressed as translocations with constantly the same break points makes it reasonable to assume that a qualitative change in the nature of a mutation or a position effect is also involved. The change in chromosome phenotype called prosomi-zation, referred to above in connection with the t(X;ll) and first described in the t(8;14) of the Burkitt lymphoma (MANOLOVA et al 1979) is undoubtedly suggestive. Whatever significance the chromosome breakage may have in cancer development, it is notable that one of the break points found in 100 % of the cells of the present leukemia is located in the same band as the deletion that has a decisive (secondary?)…”
Section: Chromosome 11 Markersmentioning
confidence: 96%
“…All patients had a deletion of the long arm of chromosome 5 as revealed by conventional trypsin-Giemsa staining. Utilization of early mitotic stages for Gband analysis (MANOLOVA et al 1979) was possible in 15 patients. Ideograms of the banding patterns at the 400, 600 and 900 band stages have been constructed for each chromosome (MANOLOV and MAN- OLOVA, unpubl.).…”
Section: Methodsmentioning
confidence: 99%
“…Cytogenetic and molecular genetic studies of Burkitt lymphoma have shown the presence of a reciprocal translocation involving the cMYC oncogene on chromosome 8, most commonly with the Ig heavy chain gene locus on chromosome 14 (Manolova et al, 1979). Less frequently, the translocation involves the IG chain gene loci on chromosomes 2 and 22.…”
Section: Burkitt Lymphomamentioning
confidence: 97%